Case report of successful treatment of patient with high gastrointestinal fistulas with tertiary peritonitis and severe abdominal sepsis - A. E. Demko; S. A. Shlyapnikov; G. I. Sinenchenko; V. I. Kulagin; I. M. Batyrshin; V. M. Luft; G. A. Pichugina; D. S. Sklizkov; Ju. S. Ostroumova; A. V. Osipov (Вестник хирургии имени И.И. Грекова, 2019)
This article is about the successful treatment of the patient with such heavy complications of a perforative duodenal ulcer as heavy abdominal sepsis, with the subsequent formation of fistulas of gastrointestinal tract. Application of the technique of «open abdomen» using vacuum assisted closure, allowed in this case to realize the principle of «sourcecontrol» and to achieve stabilization of the condition in multiple organ failure and septic shock. It is worth noting the advantage of stage reconstructive surgical interventions to this category of patients that allows to gradually improve quality of life of the patient without high operational risks of big simultaneous reconstructive operations.